2021
DOI: 10.1186/s12962-021-00262-y
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness analysis of text messaging to support health advice for smoking cessation

Abstract: Background Smoking in one of the most serious public health problems. It is well known that it constitutes a major risk factor for chronic diseases and the leading cause of preventable death worldwide. Due to high prevalence of smokers, new cost-effective strategies seeking to increase smoking cessation rates are needed. Methods We performed a Markov model-based cost-effectiveness analysis comparing two treatments: health advice provided by general… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 42 publications
1
13
0
Order By: Relevance
“…Text messaging is also cost effective, as indicated in our report and previous research [24], and unlike other digital interventions and strategies, it does not require a smartphone (with access to applications) or other devices, such as wearables, facilitating reach to sociodemographically diverse groups [1,25]. In fact, 97% of adults own a cellphone in the United States, with high rates across all race and ethnicity, household income, and educational attainment groups [1].…”
Section: Principal Findingssupporting
confidence: 81%
“…Text messaging is also cost effective, as indicated in our report and previous research [24], and unlike other digital interventions and strategies, it does not require a smartphone (with access to applications) or other devices, such as wearables, facilitating reach to sociodemographically diverse groups [1,25]. In fact, 97% of adults own a cellphone in the United States, with high rates across all race and ethnicity, household income, and educational attainment groups [1].…”
Section: Principal Findingssupporting
confidence: 81%
“…All the information provided by the patient through the application is downloaded in real time to the electronic medical records. This program is also cost-effective, with an incremental cost-effectiveness ratio (ICER) of 7.4 euros for men and 1327 euros for women from a health perspective, 30 far from the 22,000 euros threshold calculated for the Spanish health system. 31 These results that agree with obtained by other research groups, 30 have been published previously.…”
Section: Discussionmentioning
confidence: 90%
“…Second, they allow access to information in an easy and fast way. Finally, as some research has suggested that smoking cessation support by mobile phone messages is cost-saving [ 70 , 71 ], the use of smartphone apps could be a cost-effective approach to quit smoking.…”
Section: Discussionmentioning
confidence: 99%